Diurnal variation of atmospheric electric field at the summit of Mount Fuji, Japan, distinctly different from the Carnegie curve in the summertime. Issue 8 (19th April 2015) - Kamogawa, Masashi; Suzuki, Yuko; Sakai, Rikuma; Fujiwara, Hironobu; Torii, Tatsuo; Kakinami, Yoshihiro; Watanabe, Yasuyuki; Sato, Ryoe; Hashimoto, Satoshi; Okochi, Hiroshi; Miura, Kazuhiko; Yasuda, Hiroshi; et al.
Abstract In fair weather, a clear diurnal variation of atmospheric electric field (AEF), which is distinctly different from the global diurnal variation, i.e., Carnegie curve, was observed during the summer time (July and August) of the year 2010 and 2011 at the summit of Mount Fuji, Japan (3776 m in altitude). The variation of the AEF at the summit showed a local time dependent feature, which means that the AEF increased at sunrise and decreased at sunset. This local diurnal variation is known as a mountain variation. The intensity of AEF in the daytime reached 1.5–3 times larger than that in the nighttime. From the multipoint observations of cloud images and AEF, the mountain variation was found to be attributable to the AEF generated by the positively charged top of a horizontally extensive sea of clouds below the summit. Since the sea of clouds grows with the temperature rise, the AEF variation follows local time.